PERLINDUNGAN HUKUM TERHADAP KONSUMEN JASA LAYANAN PEMINJAMAN ONLINE ILLEGAL - Artha Mahendra Putra; Rani Apriani (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
To be able to anticipate unwanted things and remain orderly, a legal umbrella was issued in the form of Financial Services Authority Regulation Number 77/POJK.01/2016 concerning Information Technology-Based Money-Lending Services (hereinafter abbreviated as POJK NO.77). The Financial Services Authority (hereinafter abbreviated as OJK) in this regulation has authority in terms of regulating all matters that must be complied with by companies engaged in online lending. Fintech is a technology that can facilitate technological needs that can facilitate today's financial needs1. Offering financial solutions through technology brings changes to people's lives in various forms that are tailored to their needs. This type of fintech P2P lending is widely used because the online loan process offered can be done quickly and easily. On the other hand, a number of illegal online loans have sprung up and are easily accessible to the public. Many violations of the law have been committed by illegal online loans to the detriment of society. This paper aims to find out legal protection efforts for consumers in online lending services. The research method used is normative method.